Dynamic modeling of multi-sided marketplaces: critical factors for customer loyalty and growth in digital retail - Santos, Anna Célia Affonso dos (2025)
In recent years, online sales through marketplaces have grown significantly, accounting for an increasingly large share of total retail sales. The platform business model not only enables marketplace companies sales growth but also offers various benefits to retailers, who benefit from the marketplaces infrastructure and reputation, and to customers who find, in a single environment, a variety of products that meet their needs. However, this change in retail also brings risks and requires strategic adjustments for companies. Aiming to enhance the understanding of this business model, the present study adopts a multi-method approach, structured around three interrelated articles. The first article contains a systematic literature review about retail multi-sided marketplaces. The second article proposes a conceptual model, based on system dynamics methodology, that shows the interactions between parties on the marketplace, after in-depth interviews with industry experts. The third article refines the conceptual dynamic model involving factors affecting customer loyalty, after a structured survey with consumers. As contributions from the studies, Article 1 proposes a framework that maps how each part of this complex system contributes to the business, while also outlining the associated risks. Article 2 proposes a dynamic conceptual model describing the characteristics that drive or inhibit the growth of this business model. Finally, article 3 identifies the strategies that companies should prioritize to expand their customer base and, consequently, increase sales. The study highlights the significant impact that the marketplace business model has generated in the market, with major implications not only for retailers\' business strategies but also with social impacts, including the employment in the sector and changes in consumer purchasing behavior